An Overview of Spintronic True Random Number Generator - Fu, Zhenxiao; Tang, Yi; Zhao, Xi; Lu, Kai; Dong, Yemin; Shukla, Amit; Zhu, Zhifeng; Yang, Yumeng (Frontiers in Physics, 2021)
True random number generator is an essential component in data encryption, hardware security, physical unclonable functions and statistical analyses. Conventional CMOS devices usually exploits the thermal noise or jitter to generate randomness, which suffers from high energy consumption, slow bit generating rate, large area and over-complicated circuit. In this mini review, we introduce the novel physical randomness generating mechanism based on the stochastic switching behavior of magnetic tunnel junctions. As compared to CMOS technologies, the random number generator based on spintronic devices can have many inherent advantages, such as simpler structure, compact area, higher throughput and better energy-efficiency. Here, we review and compare various existing schemes at the device and circuit levels to achieve high performance magnetic tunnel junctions based true random number generator. The future research trends and challenges are also discussed to stimulate more works in this area.